Prevalence of hypercementosis in a Saudi Arabian population: A cone beam computed tomography study. - Santosh R. Patil; Kazuyuki Araki; Nidhi Yadav; Huwaina Abd Ghani (Universidad de Concepción., 2018)
Objective: To determine the prevalence of hypercementosis in a Saudi Arabian population. Material and methods: A total of 642 CBCT scans from patients comprising 4471 teeth were incorporated in the study sample. All teeth were analyzed for the presence of hypercementosis in sagittal, axial and coronal plains by two qualified and experienced observers. The characteristics of the involved tooth in terms of gender, jaw and location were recorded from the CBCT scans. The obtained data were statistically analyzed using SPSS 21.0. The reliability of measurements was evaluated by kappa statistics. Results: Out of total 642 subjects hypercementosis was observed in 31 patients (4.82%) and 43 teeth (0.96%). Eight (2.68%) maxillary 1st molars, 6 (1.88%) mandibular 1st molars, 5 (1.46%) maxillary second molars, 7 (1.95%) mandibular 2nd molars, 9 (4.76%) maxillary 3rd molars and 8 (3.58%) mandibular 3rd molars were observed to have hypercementosis. Among males, 4.76% were affected with hypercementosis as compared to 4.86% of females (p=0.97). Likewise, no significant difference in the occurrence of hypercementosis was observed between maxillary and mandibular arches or between sides (p>0.05). Conclusion: The prevalence of hypercementosis in a Saudi population was found to be 4.82% with respect to patients and 0.96% with respect to teeth. No significant propensity for gender, jaw and arch side was noted.